"Ukrainian revolution" – is the scientific object or source of mythmaking - Kyrychenko, V. Ye.; Кириченко, В. Є.; ORCID: http://orcid.org/0000-0002-5497-907X (Social and Legal Sciences. - Warsaw, 2018. - Vol. 1, № 2. - P. 41-47, 2018)
У статті аналізуються методи наукового пізнання феномена революції. It has passed the century since the revolutionary events of 1917, which radically changed the historical fate of the Russian Empire and the peoples that were part of it. Anniversaries are provides an opportunity both for fresh rethinking hundred-year-old events, and for summarizing the results of the researches of the phenomenon revolution as a subject. The Decree of the President of Ukraine is ordered to honor the traditions of the struggle for the independence and unity of Ukraine and the military victory of the defenders of the native land, the creators of national statehood, the millennial history of the state formation of our people, the recognition of the historical significance of events associated with the liberation struggle of the beginning of the XX century and the establishment of Ukrainian statehood. The word "revolution" has integrated into Ukrainian reality with vigour, because Khmelnitchina is already considered today by many domestic researchers mainly in the context of the revolutionary paradigm. There is then the Ukrainian Revolution of 1917-1921, which we celebrate today. Then finally followed by a string of recent colored revolutions completing this revolutionary movement. There is a powerful populist taste, however, with the objective perception of this "revolutionary series". Populism is an instrument of politics, and it is simply impossible in State affairs without it, besides it falls on the fertile ground of mythological thinking. The modern era has demonstrated the inseparability of myth from society. The modern myth has begun to be perceived in a negative context as far-fetched, erroneous, conditional, fantastic, moreover, it has emerged as a policy instrument. A political idea generates a political mythology which establishes the contact between those who govern and those governed. Turning into symbols, they create a symbolic space in politics, in which types of decision-making can be realized, for which mythology becomes the most important element of this process. Modern historiography devoted to the phenomenon of revolution, is represented by dozens of contradictory author's approaches, which differ from each other, first of all, its attitudinal dimension. Not only the fundamental indicators of the revolution are being debated: chronology and periodization, causes and preconditions, character, driving forces, etc., the question of the very concept of revolution is in question. The theoretical views on the phenomenon of revolution with their division into methodological approaches, from Marxist to synergetic, focusing on the search for objective truths, based on a solid source ground and adequate methods of scientific cognition are analyzed in the article. However, the efforts of Ukrainian experts to study the phenomenon of revolution cause many questions and criticism. Of particular concern in this sense is the point of view of the leading experts, whose position becomes almost official and is contained in textbooks, encyclopedias, and is being widely used. Obviously, the Soviet past has created a powerful myth about the phenomenon of revolution, made it as the value of top level it in the public consciousness. Even a large number of scholars are convinced that it is only way to reach new quality and radical social change. In fact, today there are scientific-research which refute the myth of the modernization significance of revolutions. It is not revolutions, but radical reforms accelerate the development of the state in an unfriendly environment, when there is a need to defend the independence or to catch up with someone or even overtake. В статье анализируются методы научного познания феномена революции.
Kyrychenko, V. "Ukrainian revolution" – is the scientific object or source of mythmaking / Volodymyr Kyrychenko // Social and Legal Sciences. - Warsaw, 2018. - Vol. 1, № 2. - P. 41-47.
Keywords: Історія. Культура. History. Culture. История. Культура; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; революція; міф; реформи; історіографія; популізм; revolution; myth; reforms; historiography; populism; революция; миф; реформы; историография; популизм